PENILAIAN REAL PROPERTI BERUPA TANAH KOSONG DI KOTA DENPASAR PROVINSI BALI - I Gusti Agung Ananda Putra (Departement of Civil Engineering, Universitas Winaya Mukti, 2023)
This research is focused on real property in the form of vacant land. The purpose of the property valuation is for the purpose of buying and selling. This research uses a market approach and market data comparison method. The type of data used is quantitative and qualitative primary data which is divided into three types, namely: general data, special data and market data. The results showed that the market value of property objects in the form of vacant land located on Jalan Tukad Citarum Gang FI, Renon Village, South Denpasar District, Denpasar City, Bali Province using the market data comparison method is Rp. 7,500,000/m2.